Derecho y patrimonio inmaterial : tensiones y posturas críticas frente a la convención para la salvaguardia del patrimonio cultural inmaterial de 2003 (2017)
This research goal is to identify the tensions that emerge from the connections between heritage law and intangible cultural heritage. Taking as a starting point the Convention for the Safeguarding of Intangible Cultural Heritage of 2003, we will identify the various critics that have been manifested on the mechanisms stablished by this international instrument and the possible solutions for the negative situations it created, understanding that an interdisciplinary dialogue between law and heritage studies is necessary if we want to overcome the aforementioned tensions and limits. In order to do this, we will analyse three main points: i) the history of the mechanisms of international law determined to protect cultural heritage in order to understand the context in which these instruments emerge, ii) the tensions and limitations created by the interactions between intangible cultural heritage and the Convention for the Safeguarding of Intangible Cultural Heritage of 2003 taking as a case-study...